ANALISA STRES KERJA TERHADAP PENCAPAIAN TARGET TIM PENARIKAN DI BAITUL MAAL HIDAYATULLAH PERWAKILAN JAWA TIMUR - Muliansyah, Eko (Dinar : Jurnal Prodi Ekonomi Syariah, 2024)
This study aims to find out more deeply about the work stress pattern of the Baitul Maal Hidayatullah representative of East Java and how the relationship of work stress to the achievement of the target of the Baitul Maal Hidayatullah withdrawal team representative of East Java. The research was conducted with a phenomenological descriptive qualitative approach. This is done to reveal more deeply what is behind the emerging phenomena related to the object of research. Data were collected by using FGD interviews, non-participant observation and documentation. The research subjects were the Head of Human Resources, and some samples from the East Java BMH office were withdrawn as key informants. Data were analyzed by data reduction process, data presentation and conclusion drawing through data verification. To ensure that the data obtained are accurate, the researchers tested the validity of the data using triangulation techniques. Based on the research, it was concluded that stress on amyl was driven by several things, namely a. job demands in the form of targets, multi-role demands; b. relationship with the division head, c. relations with fellow employees, d. relationship with family, e. Supervision by supervisor f. working conditions. But there are things that do not stress the amil from the data above, namely the organizational structure, for the organizational structure at BMH which is a system with an organizational umbrella that does not cause stress, every amil feels that the leader is someone who has competence in achieving the target.